More than linguistic needs and more than one perspective: Reconstructing perspectives of pupils with linguistically and spatially discontinuous school biographies and drawing implications for all school stakeholders - Daase, Andrea; Rozum, Nastassia; Rubinets, Viktoriia (Glottodidactica, 2023)
In the article we argue for a reconstructive and subject-oriented approach to data collection and analysis in order to reconstruct perspectives of pupils with linguistically and spatially discontinuous school biographies as a basis for needs analysis. The paper takes an in-depth look at a narrative interview with such a pupil using the Documentary Method. Based on the analysed interview passage and with recourse to the praxeologically extended sociocultural theories of SLA, we derive initial implications for schools with pupils with migratory experiences. One crucial assumption is that, in order to create better educational opportunities for children with migratory experiences, school staff need to systematically develop contingency competence. By contingency competence we mean the sensitivity and awareness of the principal openness of human life forms and their diverse possibilities for linguistic, material, and practical expression. Conclusions are drawn on what the required competencies contain and how an inclusive school can be created.